What are the challenges of the Indonesian halāl industry in the 5.0 era? - Nurlaili Nurlaili (FEB Universitas Sultan Ageng Tirtayasa, 2023)
Indonesia has very good potential, such as the majority of the Moslim population and the growing halāl industry in Indonesia, with the such good potential it should be able to become the center of the world's halāl industry. However, there are several problems that are a challenge for the government, policymakers, and the public to be able to synergize in the development of the halāl industry in Indonesia. This article describes the challenges of the Indonesian halāl industry in the era of society 5.0. The update of this paper is a discussion of the 5.0 era of society and the development of the halāl industry, which is currently in Indonesia entering the 5.0 century. This article uses descriptive qualitative with library research methods. The results of this paper are that there are two challenges that become evaluation material for the government and policymakers, namely internal challenges consisting of the lack of human resources for the halāl industry, the low number of MSMEs that are halāl certified, and halāl product certification. The external challenges in the form of rampant global competitors and competition for the advancement of technology digitalization Halāl industry, Indonesian challenges, society 5.0